Rancang Bangun Mesin Penyangrai Biji Kopi Dengan Sistem Kontrol Suhu Otomatis - Muhammad irwan; Panggabean, Hasbullah (Jurnal Teknik Mesin Indonesia, 2024)
This research aims to enhance the quality of coffee bean roasting in Indonesia by designing an automated control-based roasting machine. The machine serves as a solution to the constraints of traditional roasting processes, particularly prevalent in rural areas. In the context of Indonesia's substantial coffee production, being one of the world's largest producers, the coffee bean roasting machine is anticipated to improve efficiency and consistency in the final product. The research methodology employs a design approach, utilizing tools such as lathes, grinders, and welding machines. Materials include a power window motor, hollow iron, angle iron, and other components. The design process comprises several stages, including the construction of the machine frame, agitator design, and the implementation of an automatic control system. Machine testing results indicate roasting levels within standard parameters for light, medium, and dark roasts. The temperature-time comparison graph illustrates consistent temperature changes throughout the roasting process. In conclusion, the coffee bean roasting machine exhibits significant potential to enhance the quality and efficiency of coffee roasting in Indonesia. By incorporating post-harvest technology, it is expected to contribute significantly to increasing the value of agricultural commodities and the overall economic well-being of communities